Jig and fixtures for press machine / Wan Ahmad Faris Wan Mohd Kamaluddin - Wan Mohd Kamaluddin, Wan Ahmad Faris (2022)
Jig and fixtures are specifically intended to ensure that a large number of identical components may be machined or assembled, as well as component interchangeability. The main objective is to design jig and fixture for mechanical engineering student in Campus Bukit Besi. This is because of the limitation of design jig and fixture at the laboratory. Second objective is to fabricate U-shape jig with aligning rod. The available jig at workshop will need the user to align the upper part and lower part before pressing, with this jig and fixture, it will make the job more easier because new aligning rod is made. The material used is mild steel and the tool used in this project is only cutting and welding. My expected result is to fabricate U-shape jig and fixture with aligning rod for mechanical student and for mechanical workshop